BioApp: A Mobile Augmented Reality Application to Enhance Junior High School Students’ Academic Performance in the field of Ecological Relationship in Biology. - Baldiviano, Jordan Gregor A; Delgado, Joseph Adriann P; Mora, Joshua O (LPPM STIKI Malang, 2024)
This study investigates student difficulties in understanding biology concepts, particularly during the transition from basic topics like sexuality to complex areas such as genetics. Challenges include reduced engagement and participation, leading to lower performance in assessments. To address these issues, researchers propose